Slang as a defining feature of communicative style in Kazakh and English youth discourses (Eurasian Journal of Philology Science and Education, 2016)
The article proves the existence of a special communicative style in youth discourse. The bright characteristics of the style, i.e. use of slang, is considered on the basis of English and Kazakh youth. In the paper slang is studied in the range of lexical units which cover the term «Slanguage» (Slang language). As a result of discourse analysis of the recorded youth speech, there were defined and compared frequency and its variation depending on age group and gender of participants of communication in the English and Kazakh youth discourses. Thus, the scrutiny showed that in the English discourse majority of slang is nouns, they prevail over adjectives and verbs. In Kazakh most of slang belongs to verbs, then nouns and adjectives. In Kazakh youth discourse dirty words dominate in male youth discourse, and it cannot be often observed in female youth discourse. However, in English youth discourse this indicator varies due to age subgroups of the young.
Keywords: youth discourse; slang; discourse analysis; Kazakh youth discourse; English- speaking youth discourse; Slanguage; youth communicative style.